PENGARUH KUALITAS PRODUK, RELATIONSHIP QUALITY, BRAND EXPERIENCE DENGAN KEPERCAYAAN SEBAGAI VARIABEL INTERVENING TERHADAP KEPUTUSAN PEMBELIAN PADA BUTIK RESAARE SUMENEP - Fatikasari, Sheila Rizky; Zakki, Nurdody (Aktiva : Jurnal Akuntansi dan Investasi, 2024)
Resaare Boutique is a self-manufacturing boutique using its own premium quality brand that is ready to use and consumers can order according to their needs and desires. The purpose of this research is to research and analyze the influence of product quality, relationship quality, brand experience and trust as intervening variables on purchasing decisions. This type of research is quantitative research, with the population being the people of Sumenep. The sampling technique in this research uses purposive sampling, namely determining the sample according to criteria, namely customers/consumers of Resaare Boutique. Data collection was carried out using questionnaires and observations. The data analysis used is Descriptive Statistical Test, Research Instrument Analysis, Classical Assumption Test, Multiple Linear Regression Test, and Hypothesis Testing. The results of this research show that the variables Product Quality, Relationship Quality, Brand Experience have a significant effect on Trust. The Trust variable has a significant effect on Purchasing Decisions. The variables Product Quality, Relationship Quality, Brand Experience have a significant effect on Purchasing Decisions. And the mediation results show that the mediating variable Trust can mediate the influence of Product Quality, Relationship Quality, Brand Experience on Purchasing Decisions